US vs. Them the failure of globalism - Bremmer, Ian 1969- (Portfolio/Penguin, 2018)
"From bestselling author and TIME Magazine columnist Ian Bremmer, a definitive guide to understanding the global wave of populist nationalism. From political upheaval in Europe and the United States to an explosion of anger in the developing world, social and political turmoil has dominated recent headlines. What explains public rejection of the entire political establishment in country after country? What does this mean for the future of the United States? For the European Union? How will rising powers like China, India, and Russia manage the building pressures? How high will this wave rise before it crashes? Globalism has winners and losers, and today's globalist administrations have failed to listen to the losers. Those who have seen their jobs disappear as a result of increased immigration and relatively open trade are understandably unsympathetic to the claims that globalism is good for everyone. And now that technology gives the losers a glimpse of the winners' slice of the pie, the losers are pushing for a more equal share. Some governments will respond to these pressures with digital-age tools of repression. Others will find creative new ways to rewrite the contract that binds citizens and the state. What does this all mean for democracy, free trade, and the future of the international order? No one is better suited to explore these questions than Ian Bremmer, who has built his career on assessing global risk and explaining complex political dynamics in accessible terms. Bremmer argues that the globalists have failed to respond to the real concerns of their critics and that there is no chance for a do-over; Public demand for political transformation is inevitable. Citizens, the state, and the private sector in some parts of the world will invent and adapt. Other nations will fail. This book offers a guide to navigating the shifting political landscape and weathering the growing storm".